Gabungan Quenching-Variasi Tekanan Shot peening Terhadap Kekerasan Permukaan dan Struktur Mikro Permukaan Baja S45C - Bambang Hari Priyambodo; Margono Margono; Rizqi Ilmal Yaqin (Quantum Teknika : Jurnal Teknik Mesin Terapan, 2022)
The combination of Quenching and Shot peening (SP) heat treatment is rarely carried out, especially the use of this treatment can improve the mechanical properties of medium carbon steel (S45C). This study aims to analyze the microstructure and hardness of S45C steel with the combined effect of Quenching heat treatment with shot peening with variations in compressor air pressure. Commercial S45C steel is quenched with a heating temperature of 910oC and held for 15 minutes. In comparison, the SP process is carried out after the quenching process with variations in air pressure, namely 4, 5, 6, and 7 bar. Analysis of the combined results of Quenching and SP processes using hardness and microstructure. The investigation analysis results obtained specimens with the highest surface hardness in the quenching and SP treatment of 899.44 HV. The impact of SP on the surface up to a distance of 120 m from the surface. The highest hardness was in the Quenching and SP treatment with a pressure of 7 bar. The results of this study are used as parameter contributions in the area of surface treatment and heat treatment of carbon steel to be developed in the automotive industry.